RISIKO DAN MANAJEMEN RISIKO PADA PERBANKAN SYARIAH - Januddin Januddin; Muhammad Al Mustafa (STISNU Aceh, 2022)
An account officer will definitely face various risks related to disbursed financing. Risk is defined as a deviation from the realization of the plan that has been set as a target that may occur unexpectedly. Therefore, all companies, including Islamic banking, must have management of the risk itself. This study aims to determine the risk and management of risk in Islamic banking. The method used is literature study. The results of the study show that these risks can be classified into 2 groups, namely, first: systematic risk, second: nonsystematic risk. In this case Islamic banks make various efforts in the risk management process by developing written procedures that reflect the overall strategy and ensure its implementation. The procedures made must contain policies to identify, measure, and control risks in all banking activities including. The target of this risk management policy is to monitor and control the course of financing distribution activities with a reasonable level of risk in a directed, integrated and sustainable manner.